Improved flame retardant properties of HIPS/ATH system by organo Fe-montmorillonite. Issue 2 (1st July 2015) - Zhang, Xingguang; Zhang, Junhao; Yan, Shuai; Li, Yanjun; Kong, Qinghong
Abstract : The high impact polystyrene nanocomposites (HIPS) with aluminium trihydroxide (ATH) and organo-modified Fe-montmorillonite (Fe-OMT) were prepared by melting intercalation. The nanocomposite structures were characterized by X-ray diffraction and transmission electron microscopy. The results show that the intercalated and exfoliated nanocomposites were formed. Accordingly, the thermal stability and flame retardant properties were evaluated by thermogravimetric analysis, limiting oxygen index, UL94, cone calorimeter test. The results indicated that the nanocomposites had excellent thermal stability and the char yield was also improved. When 4wt% organo-modified Fe-MMT was added in the HIPS/ATH(46wt%) composites, the nanocomposites can achieve UL94 V-0 grade. The heat release rate, total heat release, and mass loss rate of the nanocomposites were reduced. Furthermore, the addition of Fe-OMT could further improve the smoke suppression property of HIPS composites. The improved flame retardancy by Fe-OMT in HIPS/ATH matrix maybe form reinforced char layer which prevents the diffusion of the oxygen and decomposed organic volatiles in the flame during combustion.